Capital Asset Pricing Model (CAPM) Analysis: Technology Sector Stock Conditions Before and During the Pandemic - Rizky Ramadhoni, Refindi; Matoati, Rindang; Rahmawati, Siti; Kaewlaead, Chuta; Juwita Ermawati, Wita (IPB University, 2024)
The COVID-19 pandemic made people more active in saving, such as investing in the capital market. Stocks in the technology sector were excellent stocks because the trading volume increased by up to 7.3 times during the pandemic. The Capital Asset Pricing Model (CAPM) was a model to see the expected rate of return and aimed to assist investors in making investment decisions. CAPM used beta (β) to measure the sensitivity a stock or portfolio is to market movements. Beta indicates the tendency of an asset's return to react to fluctuations in the overall market. This study aimed to look at differences in technology sector stocks in the period before and during the pandemic using the CAPM method and paired t-test. The research using a purposive sampling method. A quantitative descriptive method was used in this study and used secondary data in the form of financial statements of technology sector companies listed on the Indonesia Stock Exchange. Based on the results of the study, seven stocks had an average negative return before the pandemic and positive returns during the pandemic. There was one efficient stock in the pre-pandemic period and six inefficient shares, and seven shares were classified as efficient shares during the pandemic. The results of the paired t-test showed that there was a significant difference between individual returns before and during the pandemic.